Estimating the Cost of Youth Disengagement in New Zealand - Gail Pacheco; Jessica Dye (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2013)
Youth exclusion, disengagement, and overall underutilisation in the labour market has short term costs to the economy, as well as long term impacts on society. In this research we project the loss to productivity, measured in foregone wages, and the expected cost to public finances for NZ and Auckland youth aged 15-24 not in employment, education, or training (collectively known as NEET). We estimate the expected per capita cost of each NEET youth in NZ is approximately 26,847 over the next 1-3 years. The analogous cost for the Auckland cohort is found to be higher, due largely to higher foregone wages. Closer inspection reveals that Auckland NEET youth of Maori and Pacifica descent are associated with relatively high per capita costs compared to their NZ European counterparts. This result is driven by the greater propensity of Maori and Pacific Peoples to disengage from the education system earlier, to withdraw from the work force due to caregiving responsibilities at a younger age, and to experience longer durations of unemployment than their NZ European counterparts. The sizeable estimated costs associated with NEET youth highlight the urgent need for policy intervention directed at improving transitions from NEET status to the workforce, or further education/training.
Keywords: J64; J24; 330; NEET; youth disengagement; economic productivity; labour market; transition to work